FAMILY VIOLENCE IN CLASSICAL AND IGBO LITERATURES (2012)
Classical and African literatures have portrayed the family as a nucleus of the societies. Existing studies from the old Graeco-Roman times and Igbo cultures acknowledged this significance by paying adequate attention to issues of marriage, inheritance, finance, and social class in their literatures. However, hardly any one of these studies has exclusively concentrated on or compared the representations of family violence in the literatures. This study therefore, examines the causes, manifestations and effects of family violence in the Classical and Igbo literatures with a view to highlighting their convergences and divergences. Using the descriptive and comparative research design, the study adopts Sigmund Freud's Instinct theory of Aggression. The primary Classical sources consulted were the works of Aeschylus, Euripides, Sophocles, Suetonius and the Digests of Justinian while the works of Achebe, Ofomata, Ike, Adichie, and oral literature were consulted for the Igbo aspect, because these have large representations of family violence. Data were subjected to thematic and critical analysis. Family violence which is largely a common feature of both Classical and Igbo societies, as portrayed in their literatures, demonstrates that barrenness is hardly tolerated and is blamed on the woman. In Euripides' Andromache Hermione is repudiated and replaced with another woman on account of barrenness. Osita, Uju's husband married another wife without her consent inOnye Chi yaAkwatughi written by Ofomata. Theauctoritas of the paterfamilias sometimes constitute danger in the household, inOresteianTrilogy, king Agamemnon sacrificed his daughter Iphigenia in order to gain a favourable weather and passage across the sea. In Things Fall Apart, Okonkwo's second wife almost lost her life to his gun shot, after being seriously battered because she made a mistake during food preparation. Adichie'sPurple Hibiscus presents Mr. Eugene as a batterer of wife and children on grounds of disobedience. Ezeulu creates a domestic harshness and fear in Achebe's Arrow of God. Sophocles' Electra and Ike's Potter's Wheel show that abandonment, rejection, and child abuse are traumas which family members suffer as a result of violence. The cruel treatment of a spouse often leads to rash reactions and murder as exemplified in Aeschylus' Agamemnon, Euripides' Medea, Ovid's Metamorphoses,Adichie'sPurple Hibiscus, among others. The texts also show that false accusation, infidelity, deviant behaviours, incest and denial can both result from or into family violence. However, some cases are peculiar to Classical literature: youths directly or indirectly killing their mothers as observed in Aeschylus' Libation Bearers and Sophocles' Women of Trachis. In Igbo literature, wife and child battering (Things Fall Apart, Purple Hibiscus, andOnye Chi YaAkwatughi) is a common occurrence. While Classical literature often attributes some violent attacks to the influence of the gods, Euripides' (Bacchae) Igbo literature has no such corollary. Family violence in Classical and Igbo literatures is seated in socio-cultural, biological and economic experiences of the Graeco-Roman and Igbo peoples. Its effects scope over abandonment, battering, divorce and murder, with more cases of battering in Igbo literature; and murder and vengeance of the gods in Classical literature.